Study of the zinc action on the 2-chloroethyl 2-bromo-2-perfluoroalkylethanoates. Issue 3 (4th May 2018) - Jedidi Yaich, Balsem; Ould Amanatoullah, Abakar; Mekni, Nejib Hussein; Romdhani-Younes, Moufida
ABSTRACT: 2-Bromo-2-perfluoroalkyl acids are converted into the corresponding esters by a reaction of alcoholysis in the 2-chloroethanol. The action of zinc on perfluoroalkylated bromo-esters resulted in the bromine reduction products formation via zinc organic intermediates. When heated at 100°C, for 48 h, in the presence of an excess of zinc, the bromo-esters produce the symmetrical bis(vinyl perfluoroalkyl ester) ethoxide compounds, resulting from the BrZnF elimination reaction, followed by a dimerization reaction. GRAPHICAL ABSTRACT: